2016
DOI: 10.1002/lno.10349
|View full text |Cite
|
Sign up to set email alerts
|

Long-term alkalinity trends in the Baltic Sea and their implications for CO2 -induced acidification

Abstract: Anthropogenic CO 2 emissions currently decrease open ocean pH, but on multi-millennial time scales intensified continental weathering is expected to contribute to increasing oceanic alkalinity (A T ) and thus mitigate the acidification signal. The Baltic Sea is an ideal study site for such A T dynamics, due to its direct link to terrestrial processes, short water residence time and long history of A T measurements dating back to the early 20 th century. We compiled an extensive A T data set that revealed the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
116
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(128 citation statements)
references
References 62 publications
10
116
2
Order By: Relevance
“…There, an increase in A T of 3.4 µmol kg −1 yr −1 was observed from 1995 to 2014 (mean salinity = 7). In contrast to Point B, the increase in Baltic Sea A T was not noticeable at salinity > 30 (Müller et al, 2016).…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…There, an increase in A T of 3.4 µmol kg −1 yr −1 was observed from 1995 to 2014 (mean salinity = 7). In contrast to Point B, the increase in Baltic Sea A T was not noticeable at salinity > 30 (Müller et al, 2016).…”
Section: Discussioncontrasting
confidence: 56%
“…Positive trends in river A T have been documented in North America and occur via a number of processes including (1) the interplay of rainfall and land use (Raymond and Cole, 2003), (2) anthropogenic limestone addition used to enhance agricultural soil pH (Oh and Raymond, 2006;Stets et al, 2014) and freshwater pH (Clair and Hindar, 2005), and (3) potentially indirect effects of anthropogenic CO 2 on groundwater CO 2 acidification and weathering (Macpherson et al, 2008). These and other processes were hypothesized to have driven A T changes in the Baltic Sea (Müller et al, 2016). There, an increase in A T of 3.4 µmol kg −1 yr −1 was observed from 1995 to 2014 (mean salinity = 7).…”
Section: Discussionmentioning
confidence: 99%
“…The control scenario is by no means constant, but reflects the climate-driven changes expected according to the A1B storyline and changes in deposition of emissions from other sources following RCP4.5. Müller et al (2016) have recently reviewed the temporal development of alkalinity in the Baltic Sea, and have shown that the alkalinity is currently increasing. This may be connected to the observed increase in organic carbon concentrations (Fleming-Lehtinen et al 2015), since it has been shown that organic matter contributes to the total alkalinity in the Baltic Sea (Kulinski et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The reduction of alkalinity through the deposition of strong acids is also a potential monitoring option, but would need to assume an otherwise constant alkalinity. This assumption may not always be true: for example, a recent study has shown that the alkalinity of the Baltic Sea is increasing, presumed due to changes in runoff (Müller et al, 2016). A more promising option for monitoring the releases due to combustion of heavy fuel oil may be the metal vanadium.…”
Section: Monitoring Of Ship Plumes and Scrubbersmentioning
confidence: 99%